PROSPECTS FOR THE DEVELOPMENT OF THE UZBEKISTAN-JAPANESE EDUCATION SYSTEM - F.F. Khoshimov; R. Egamberdieva; M. F. Fayzullaeva (International Engineering Journal For Research & Development, 2020)
This article provides information about the education system of Uzbekistan and Japan, its achievements and problems, as well as about future development.